Investigating the Biocompatibility and Functionality of Acetylsalicylic Acid-Loaded GumMA Inks for the Application of Cardiovascular Grafts: Local Antithrombotic Drug Delivery Platform - Izbudak, Burcin; Dastjerd, Samin; Donmez, Mustafa; Kocaaga, Banu; Guner, Fatma Seniha; Bal-Ozturk, Ayca (AMER CHEMICAL SOC, 2025)
The current study aims to provide new solutions in cardiovascular tissue engineering through formulating methacrylated gellan gum (GumMA)-based hydrogel grafts with respect to 2, 3, and 3.5% polymer contents while incorporating acetylsalicylic acid (ASA) as an antithrombotic agent, tailored through three-dimensional (3D) bioprinting technique and photo-cross-linking with Irgacure 2959 under UV to enhance mechanical features, biocompatibility, and therapeutic efficacy. The investigation assessed GumMA's concentration impact on physicochemical characteristics and in vitro biological performance of the hydrogels, in which the results revealed that the swelling ratio decreased by increasing the polymer content while maintaining structural stability over time in phosphate-buffered saline (PBS) and simulated body fluid (SBF) mediums that contributed to the observed ASA biphasic release profile. Furthermore, the system exhibited excellent hemocompatibility and nontoxicity toward human umbilical vein endothelial cells (HUVEC), and its hemostatic capacity was investigated through hemolysis and coagulation analysis. Based on these findings, the developed grafts are promising candidates for use as bioengineered vascular grafts with a long-term functional performance.
Keywords: RHEOLOGICAL PROPERTIES; CROSS-LINKING; HYDROGEL; BEHAVIOR; METHACRYLATE; NETWORKS; DENSITY; ASPIRIN; CREEP; Biochemistry & Molecular Biology; Chemistry; Polymer Science